Exploring the spatial dimensions of rural development models in Malaysia 1957-2007 - Fredericks, L.J. (2009)
Malaysia, a relatively small country, gained independence from Britain in 1957 after a lengthy colonial rule and the national government began an economic restructuring process to become a developed country. The initial rural development push to rectify the colonial policy of benign neglect of the Malay, rural,peasant sector rested on the urban industrial growth models in neoclassical growth theory. Integrated rural development was the second approach, conceptually fuzzy and diffuse. Broader policy formulations followed anchored on multiple policy interventions approximately focused on rural poverty. In these policy formulations, the notions of geography, space, place and territory the Spatial dimensions- in rural development gradually emerged in the regional development area and growth poles approaches. Regional growth corridors (an extension of the agropolitan model) reflecting a deepening sensitivity to territorial, population and global dynamics (Terluin,2003) are the current policy Instruments. These rural development processes and their spatial dynamics in Post-independent Malaysia are explored in this paper.